2013
DOI: 10.1042/cs20130284
|View full text |Cite
|
Sign up to set email alerts
|

Serum 25-hydroxyvitamin D predicts the short-term outcomes of Chinese patients with acute ischaemic stroke

Abstract: Low vitamin D levels have been reported to contribute to the risk of cardiovascular events and mortality, especially stroke. In the present study we therefore evaluated the short-term prognostic value of serum 25(OH)D (25-hydroxyvitamin D) in Chinese patients with AIS (acute ischaemic stroke). From February 2010 to September 2012, consecutive stroke patients admitted to the emergency department at two hospitals in Beijing, China were identified. Clinical information was collected, and the serum concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
70
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 43 publications
12
70
0
Order By: Relevance
“…These findings were consistent with those of previous studies, which showed 68-78% prevalence of vitamin D deficiency in the Chinese acute ischemic stroke population [14,15] . Our findings have confirmed the results of the previous studies, which suggested that 25(OH) D is a prognostic marker of functional outcome and death in patients with acute ischemic stroke and hemorrhagic stroke [13,14] .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These findings were consistent with those of previous studies, which showed 68-78% prevalence of vitamin D deficiency in the Chinese acute ischemic stroke population [14,15] . Our findings have confirmed the results of the previous studies, which suggested that 25(OH) D is a prognostic marker of functional outcome and death in patients with acute ischemic stroke and hemorrhagic stroke [13,14] .…”
Section: Discussionsupporting
confidence: 83%
“…The MESA study demonstrated that vitamin D deficiency is associated with incident coronary heart disease in white or Chinese but not in black or Hispanic participants [12] . Recently, a few studies have suggested the association between vitamin D status and functional outcome of acute stroke [13][14][15] . However, it remains to be determined whether a low vitamin D level is associated with stroke outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D deficiency and insufficiency (77.5%) was very common in our patients. Median baseline 25(OH)D levels 14.03ng/ml in our patients were similar compared with other studies 15.2ng/ml 14 and 14.1 ng/ml 15 . Pathophysiological mechanisms remain speculative, but several possible biological mechanisms might explain the association of low 25(OH)D with poor outcome 16 .…”
Section: Discussionsupporting
confidence: 73%
“…In our study, we found that circulating serum 25(OH)D levels were deficient and insufficient in 77.5 % of patients with acute stroke. Another study in Chinese patients also found that vitamin D deficiency (78.6 %) was very common 15 . Tu et al also suggested that 25(OH)D was an independent predictor of major disability and death within 90 days after onset of ischemic stroke with ORs (95% CIs) of 0.79 (0.73-0.85) and 0.70 (0.50-0.98) respectively 16 .…”
Section: Resultsmentioning
confidence: 98%
“…A further study in China not only showed that patients with acute ischaemic stroke had significantly lower vitamin D levels compared to controls, but also that vitamin D levels were a prognostic marker of short-term functional outcome and death in stroke patients (Tu et al, 2014).…”
Section: Strokementioning
confidence: 99%